On the sensitivity of event-related fields to recollection and familiarity - Evans, Lisa H.; Wilding, Edward L. (Elservier, 2018)
The sensitivity of event-related potentials (ERPs) to the processes of recollection and familiarity has been explored extensively, and ERPs have been used subsequently to infer the contributions these processes make to memory judgments under a range of different circumstances. It has also been shown that event-related fields (ERFs, the magnetic counterparts of ERPs) are sensitive to memory retrieval processes. The links between ERFs, recollection and familiarity are, however, established only weakly. In this experiment, the sensitivity of ERFs to these processes was investigated in a paradigm used previously with ERPs. An early frontally distributed modulation varied with memory confidence in a way that aligns it with the process of familiarity, while a later parietally distributed modulation tracked subjective claims of recollection in a way that aligns it with this process. These data points strengthen the argument for employing ERFs to assess the contributions these processes can make to memory judgments, as well as for investigating the nature of the processes themselves.